DIE LISZTSCHE IRONIE IN DER SCHILDERUNG DES „MEPHISTOPHELISCHEN“ IM DRITTEN TEIL DER „FAUST-SYMPHONIE“ - Miklós FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
The third part (Mephistopheles) of the Faust-Symphony by Liszt brings the transformation and the caricature of the first part (Faust), and hereby the undisguised musical portrayal of the ugliness and the maliciousness, as two of the fundamental ethic and aesthetic (negative) values of the Romanticism. The musical analysis intends to identify and exemplify the most important lisztian procedures, through which the thematic material presented in the musical discourse of the Faust part will be mocked and distorted by the Mephistophelian character.